INFLAMMATORY BOWEL DISEASE: CYTOCHEMICAL ACTIVITY OF INTRACELLULAR ENZYMES OF PERIPHERAL BLOOD NEUTROPHILS AND MONOCYTES IN DIAGNOSIS - V. A. ЕMELYANOVA; A. A. DEMIDOV; N. V. KOSTENKO; E. N. CHERNYSHEVA (Кубанский научный медицинский вестник, 2017)
Aim. To carry out literature analysis devoted to the studies of the importance of peripheral blood neutrophils and monocytes in the pathogenesis and diagnosis of inflammatory bowel diseases, namely Crohn's disease and ulcerative colitis. Blood neutrophils and monocytes, as the main components of the inflammatory infiltration of the intestinal wall, are the sources of inflammatory mediators, pro-inflammatory cytokines, involved in the mechanisms of the mucous membrane destruction. Change of these blood cells intracellular enzymes activity using cytochemical methods can indicate the activity of the systemic inflammatory process, which reflects the activity of this process in the intestinal wall, and make possible prognosis of the disease course.Conclusion. Further study of the dynamics of the functional activity of blood neutrophils and monocytes will make possible design of diagnostic algorithms for inflammatory bowel diseases and assess the effectiveness of the therapy.